Heidegger and the media - Gunkel, David J.; Taylor, Paul A. 1967- (Cambridge, UK Malden, MA Polity Press, 2014)
The most significant philosopher of Being, Martin Heidegger has nevertheless largely been ignored within communications studies. This book sets the record straight by demonstrating the profound implications of his unique philosophical project for our understanding of today's mediascape. The full range of Heidegger's writing from Being and Time to his later essays is drawn upon.
Introduction -- We need to talk about media -- Mediated truth -- In medias res -- The dasign of media apps : the questions concerning technology -- Conclusion : there is nothing outside technology.
Includes bibliographical references (pages 177-190) and index.
Keywords: Heidegger, Martin -- 1889-1976 -- Criticism and interpretation; Mass media -- Philosophy; Mass Media